ABCD Approuch In Financial Literacy Assistance of Sunyalangu Village Communities, Banyumas - Hilyatin, Dewi Laela; Raharja, Mahardhika Cipta; Azah, Istiani Nurul; Nurhalimah, Siti; Fatimah, Siti Nur; Febriaeni, Riska Linda; Riadi, Rian Sugeng (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2025)
The literacy of Indonesian society is still relatively low, this is due to a fairly low interest in reading and motivation. One of the important literacies for the community is financial literacy. Because this is a form of long-term investment, especially in financial management. So important is financial literacy for the community, it is necessary to do mentoring that focuses on financial literacy, especially for rural communities. Because the level of financial literacy of rural communities is lower than urban communities. Sunyalangu Village, Karanglewas District is currently a pilot Inclusion Village launched by the Financial Services Authority Purwokerto since 2021. To be able to support government programmes, as an Educational Institution, UIN SAIZU Purwokerto must be present. Moreover, one of the faculties under UIN SAIZU Purwokerto is Economics. ABCD approach community service on financial literacy in Sunyalangu Village, Banyumas Regency was conducted for two months. The service team consisting of lecturers and students partnered with youth karangtaruna and the Sunyalangu village government. There are several stages carried out in the service process, namely: pre-service, implementation of assistance, and post-assistance. At the beginning of the service the team measured the level of community financial literacy. After knowing the level of community financial literacy, the service team carried out the service process and took measurements again. after the service was carried out, the level of community financial literacy was 71%, which means moderate. The community said that the service carried out was very beneficial to them, especially in terms of financial literacy.